Representações e estereótipos sobre a tradução português/espanhol - Simão, Angélica Karim Garcia [UNESP] (UNICAMP. Departamento de Linguística Aplicada, 2014)
This work is aimed at discussing stereotypes in about the translation Spanish and Portuguese, seeking to problematize the relationship among utterances produced by Brazilian, Spanish and Argentine undergraduate students from different contexts of graduation in translation. In order to do so, the term and concept of stereotype were initially delimited, the latter understood as a representation that ascribes to a perspective of reality as homogeneous, in a process of cognitive simplification, and its ramifications in studies throughout the twentieth century. Subsequently, based on the data collected from classes of a Translation undergraduate course in Brazil, I discuss which stereotypes are related to the translation of the Spanish language, using techniques developed to conduct the empirical and structural analysis of social representations. These stereotypes are finally compared to utterances about the translation of Portuguese language produced by students of Portuguese translation from two different contexts, namely the course Traductorado en Portugués (Buenos Aires - Argentina) and Traducción e Interpretación (Granada - Spain). The different levels of data analysis are based on theoretical works from Social Psychology and Enunciative Semantics. They enabled me to identify a syntactic-enunciative mode characterized by outlines and contradictions, which in turn avoided direct statements by Brazilian students, revealing a saying markedly polyphonic. In spite of some similarities in the argumentative mode, the representations made by Spaniards and Argentines are distant with respect to the objects of valuation embedded to the Portuguese language.

Pretende-se discutir a questão dos estereótipos a respeito da tradução da língua espanhola e portuguesa buscando-se problematizar a relação entre os enunciados produzidos por estudantes brasileiros, espanhóis e argentinos de diferentes contextos de formação em Tradução. Para tanto, delimitamos inicialmente o termo e o conceito de estereótipo, entendendo o segundo como uma representação - de caráter homogeneizador - atribuída à realidade, em um processo de simplificação cognitiva, e os seus desdobramentos dentro de estudos ao longo do século XX. Posteriormente, apresentamos quais são os estereótipos relacionados à tradução da língua espanhola levantados em um curso de Tradução brasileiro, Bacharelado em Letras-Tradutor, a partir de pesquisa empírica, utilizando-se técnicas desenvolvidas para realizar a análise estrutural das representações sociais. Para finalizar, contrapomos os estereótipos citados anteriormente aos enunciados sobre a tradução da língua portuguesa formulados por estudantes de tradução de língua portuguesa provenientes de dois contextos diferentes, a saber: o curso de Traductorado en Portugués (Buenos Aires - Argentina) e o curso de Traducción e Interpretación (Granada - Espanha). Os diferentes níveis de análise dos dados apoiaram-se teoricamente em trabalhos da Psicologia Social e na Semântica Enunciativa, e permitiram identificar um modo sintático-enunciativo marcado por contornos e contradições, que evitou a afirmação direta, caracterizando um dizer marcadamente polifônico, no que concerne aos enunciados brasileiros. Embora com algumas semelhanças no modo argumentativo, as representações feitas por espanhóis e argentinos se distanciam no que tange aos objetos de valoração atrelados ao idioma português.
Representations and stereotypes about the translation portuguese/spanish
Keywords: tradução; estereótipos; espanhol; translation; stereotypes; spanish language